Lithic raw materials and modes of exploitation in quarries and workshops from the center of the pampa grasslands of Argentina - Messineo, Pablo Geronimo (2015)
Quarry workshops have an important economic, social, cultural, and symbolic role for past hunter-gatherer societies and the northwest Tandilia System would have represented a place of great cultural significance because human groups could have exploited a huge diversity of rocks and minerals. The main objectives in this paper are to analyze different exploitation, production, and use strategies applied on chert and silicified dolomite quarry workshops, and to interpret diverse ways of transport and circulation of these lithic raw materials from procurement areas to other sites in the center of the Pampa grasslands during the Late Holocene. The studies done suggest several modes in raw materials selection in quarries, reduction strategies, tool manufacture, and rock circulation in the landscape. It is proposed that both raw materials could have been transported from workshops to other sites in the form of nodules, different kinds of partially and/or totally decorticated cores, large flakes, and possibly tools. With the reduction of residential mobility in hunter-gatherer groups during the Late Holocene, the most exploited rocks in the center of the Pampa grasslands were those located nearest the sites, such as chert from the Sierras Bayas hills. Two procurement strategies (embedded and special trips by using logistical mobility) could have been applied on chert and silicified dolomite acquisition. On the other hand, human groups occupying territories far from quarries could have obtained them through social exchange and interaction networks.